Use of Structural Steel Frames for Structural Restoration of URM Historical Buildings in Seismic Areas - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2017)
Historic buildings and monuments are an important part of our cultural heritage that must be protected and their sustainability ensured, especially when earthquakes occur. In this paper, a technique that uses structural steel frames is proposed as one way of strengthening unreinforced masonry (URM) in historical buildings. The idea underpinning this technique is to reduce the earthquake displacement demand on non-ductile URM walls by attaching steel frames to the building floors from inside. These frames run parallel to the structural system of the building and are fixed at their base to the existing foundation of the building. Furthermore, they are constructed rapidly, do not occupy architectural space, save the building's historic fabric, and can be easily replaced after an earthquake if some minor damage ensues. The proposed technique was applied to a five-story historical masonry building in Istanbul. The results of seismic performance analysis indicate that even though the building has plan irregularities, the proposed steel frames are able to effectively enhance the building's seismic performance by reducing inter-story drifts and increasing lateral stiffness and strength.
Keywords: URM building; historical; steel frames; restoration; seismic